Deterrence from self-protection measures in the ‘market model’ of crime: dynamic panel data estimates from employment in private security occupations - Zimmerman, Paul R.
Private individuals and entities invest in a wide variety of market-provisioned self-protection devices or services to mitigate their probability of victimization to crime. However, evaluating the effect of such private security measures remains understudied in the economics of crime literature. Unlike most previous studies, the present analysis considers four separate measures of private security: security guards, detectives and investigators, security system installers, and locksmiths. The effects of laws allowing the concealed carrying of weapons (an unobservable precaution) are also evaluated. Given that Ehrlich’s ‘market model’ suggests private security is endogenous to crime, the analysis relies primarily on dynamic panel data methods to derive consistent parameter estimates of the effect of self-protection measures. The relationship between self-protection and UCR Part II Index offense (arrest) data are also considered in order to provide exploratory evidence on the interaction between publicly and privately provisioned crime deterrence efforts.Crime, Deterrence, Market model, Private Security, Self-protection